American GDP Alone Predicts Human Development - Bechtel, Gordon; Bechtel, Timothy (Advances in Social Sciences Research Journal, 2020)
Bechtel (2018, 2019) linked gross domestic product (GDP) to the United Nation’s Human Development Index (HDI). These results at the national level, and subsequent results at the global level (Bechtel, G. and Bechtel, T., 2020), induce our hypothesis that a transform of American GDP predicts global HDI. This hypothesis is confirmed by two distinct bilinear regressions in which global HDI is predicted by American GDP alone. These empirical findings contribute to the socioeconomic and philosophical debate on the nature of well-being. They also show that HDI computation can be carried out from American GDP without survey sampling, questionnaire interrogation, probabilistic inference, significance testing, or even HDI data. In view of trade-war and covid-19 shocks to all national economies, international attention to American GDP is now compelling.